Correction: Flow-through solvolysis enables production of native-like lignin from biomass. Issue 24 (30th November 2021) - Brandner, David G.; Kruger, Jacob S.; Thornburg, Nicholas E.; Facas, Gregory G.; Kenny, Jacob K.; Dreiling, Reagan J.; Morais, Ana Rita C.; Renders, Tom; Cleveland, Nicholas S.; Happs, Renee M.; Katahira, Rui; Vinzant, Todd B.; et al.
Abstract : Correction for 'Flow-through solvolysis enables production of native-like lignin from biomass' by David G. Brandner et al., Green Chem., 2021, 23, 5437–5441, DOI: ; 10.1039/D1GC01591E .